SIKAP SUAMI TENTANG KEKERASAN SEKSUAL PADA PASANGAN - Sunaringtyas, Widyasih (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
A husband's attitude regarding sexual violence to a partner can be seen in how the husband views his wif, if the husband looks down on his wife, the husband will usually have less respect for the wife as a patner, as a family member or as a sexual couple. The aim of this research was to determine husbands' attitudes regarding sexual violence to couple in Bendo Lor Hamlet RT 02 RW 07 Bendo Village, Pare District, Kediri Regency.This research design used quantitative descriptive, with variables single namely husband's attitude regarding sexual violence to couple, the research population was 43 respondents in Bendo Lor Hamlet, rt 02 RW 07, Bendo Village, Pare sub District, Kediri Regency. The sampling technique used was total sampling, this research was conducted from 19 to 25 March 2024, the research instrument used a questionnaire. The data was analyzed using percentages and interpreted to obtain quantitative data.The results of the research from 43 respondents showed that the majority of respondents, namely 22 respondents (51%), had good criteria for husbands' attitudes about sexual violence in their couple and almost half of the respondents, namely 21 (49%) had sufficient criteria.A total of 22 respondents (51%) had good attitude criteria, the influencing factors were emotional patience, income, length of marriage, number of children and 21 respondents (49%) had sufficient attitude criteria, namely living together, age, job.Respondents are expected to increase their insight by reading references about husbands' attitudes towards sexual violence against partners so that they can take a better about attitude, apart from that, they also need to improve communication within the family in order to maintain the continuity of the household.